The Impact of Standards of Government Accounting, Accounting Information Processing Systems, and Human Capital Competency On Financial Reporting Quality at Local Government Agency for Finance and Asset Affairs (BKAD) Local Government of Bandung Regency - Alfarabi, Farah Fadilah; Damayanti, Santi (Journal Research of Social Science, Economics, and Management, 2025)
This study examines the impact of Standards of Government Accounting, Accounting Information Processing Systems, and Human Capital Competency on Financial Reporting Quality at Local Government Agency for Finance and Asset Affairs (BKAD) Local Government of Bandung Regency. A quantitative approach was utilized, combining descriptive analysis with verification techniques to examine the research objectives. The study utilizes primer data collected directly from 34 respondents as its primary data source, and the data were analyzed using multiple regression analysis, processed through SPSS software. The results are both individually and simultaneously, Standards of Government Accounting, Accounting Information Processing Systems, and Human Capital Competency significantly impact Financial Reporting Quality. These findings underscore the essential role of implementing standards effectively, robust accounting systems, and competent personnel in enhancing the financial reporting quality within local government institutions.